(untitled) (Clinics, 2014)
Solid organ transplantation has transformed the lives of many children and adults by providing treatment for patients with organ failure who would have otherwise succumbed to their disease. The first successful transplant in 1954 was a kidney transplant between identical twins, which circumvented the problem of rejection from MHC incompatibility. Further progress in solid organ transplantation was enabled by the discovery of immunosuppressive agents such as corticosteroids and azathioprine in the 1950s and ciclosporin in 1970. Today, solid organ transplantation is a conventional treatment with improved patient and allograft survival rates. However, the challenge that lies ahead is to extend allograft survival time while simultaneously reducing the side effects of immunosuppression. This is particularly important for children who have irreversible organ failure and may require multiple transplants. Pediatric transplant teams also need to improve patient quality of life at a time of physical, emotional and psychosocial development. This review will elaborate on the long-term outcomes of children after kidney, liver, heart, lung and intestinal transplantation. As mortality rates after transplantation have declined, there has emerged an increased focus on reducing longer-term morbidity with improved outcomes in optimizing cardiovascular risk, renal impairment, growth and quality of life. Data were obtained from a review of the literature and particularly from national registries and databases such as the North American Pediatric Renal Trials and Collaborative Studies for the kidney, SPLIT for liver, International Society for Heart and Lung Transplantation and UNOS for intestinal transplantation.